2017
DOI: 10.1002/ajs4.6
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational care as a viable intervention strategy for children at risk of delinquency

Abstract: Literature has consistently cited early childhood interventions as an effective method for mitigating or preventing future delinquency in at-risk children. In this manuscript,we propose an adapted model of Intergenerational Care presenting as a possible intervention strategy for children at risk of delinquency. This model of care draws from programmes that provide formal care and support for older people and young children, with a primary focus on intergenerational interactions that focus on respite day care, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 80 publications
(107 reference statements)
0
12
0
Order By: Relevance
“…For consumers, the models may increase the quality of life of participants and encourage the creation of age-friendly communities in Australia. For participants, InGen programs may: improve motor and cognitive skills; social inclusion; delay entry into nursing homes; improve academic performance of at risk children; and increase social engagement, confidence and resilience in participants (Cummings et al 2002;DeVore et al 2016;Femia et al 2008;Whitten et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For consumers, the models may increase the quality of life of participants and encourage the creation of age-friendly communities in Australia. For participants, InGen programs may: improve motor and cognitive skills; social inclusion; delay entry into nursing homes; improve academic performance of at risk children; and increase social engagement, confidence and resilience in participants (Cummings et al 2002;DeVore et al 2016;Femia et al 2008;Whitten et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These programs have also been shown to increase social engagement, confidence, and resilience (Femia et al 2008;Hayes 2003). Research on the lifecourse theory identifies the importance of adult support structures early in childhood to improve confidence, security and lower incidences of bullying and antisocial behaviour (Whitten et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to younger age groups, IGPs may increase their life satisfaction [56, 57], advance their prosocial behaviour [58], and keep them away from delinquency [59]. Moreover, IGPs seem to be effective in increasing youngsters' awareness of older people's needs, by helping them overcome age-related stereotypes more easily [28, 60], and promoting a positive attitude towards the older counterpart [45].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the academic field, many researchers have found that intergenerational exchange improved school engagement and decreased school absenteeism [ 44 ]. Moreover, children and adolescents can also benefit from intergenerational programs by providing access to adults at difficult times, reducing involvement in offending behavior and drug use, and improving personal resilience [ 45 ].…”
Section: Discussionmentioning
confidence: 99%